McDonald’s Observation - Aldrich, H. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Goals of the assignment: to observe the interaction at a fast food restaurant (preferably McDonald’s, but it could be another one, such as Burger King, Chik-Fil-A or Hardies, but NOT a pizza restaurant) and describe what you see.